Single Incision Laparoscopic‐Assisted Intestinal Surgery (SILAIS) in 7 Dogs and 1 Cat. Issue 5 (22nd April 2013) - Case, J. Brad; Ellison, Gary
Abstract: Objectives: To describe the clinical findings and short‐term outcome in 7 dogs and 1 cat undergoing single‐incision laparoscopic‐assisted intestinal surgery (SILAIS) using an SILS™ or EndoCone™ port. Study Design: Prospective case series. Animals: Dogs (n = 7) and cat (n = 1). Methods: An SILS™ port using three 5‐mm instrument cannulas or EndoCone™ port was used to perform an initial limited laparoscopic abdominal exploration. The stomach and descending duodenum were explored intracorporeally and the jejunum through orad descending colon was explored extracorporeally. All intestinal procedures (enterotomy, biopsy, resection, and anastomosis) were performed extracorporeally. Omentalization of affected bowel was accomplished either intracorporeally or extracorporeally. Short‐term outcome was determined. Results: SILAIS was completed successfully in all but 1 dog and all animals had a good short‐term outcome. Most (n = 5) animals were discharged the day after surgery. SILAIS was performed in a median of 120 minutes (interquartile range; 82–148 minutes) and was associated with a moderate level of difficulty. No major complications occurred but conversion to celiotomy (n = 1) and enlargement of the incision (n = 3) was required because of inability to exteriorize the affected bowel. Conclusions: SILAIS using an SILS™ or EndoCone™ port in dogs and cats is feasible and appears effective in selected cases. Single portal laparoscopic‐assisted intestinal surgery might be an effective method of minimizing morbidity in dogs and cats with uncomplicated intestinal disease.